Meningeomas - Landa Cannon, Rodolfo (1964)
In the stories of 35 cases of patients with intracranial meningeomas served at the NIE, we have studied the following: history of patients, sex, age, location of tumor, symptoms, giving special attention to the most common symptoms: headache , epilepsy, visual disturbances, mental disorders, motor disturbances, sensory disturbances and presence of extracranial tumor period prior to admission of patients disease; most common findings on clinical examination; radiology, electroencephalography, treatments used, survival after surgical treatment of the same value and considering the conditions of survival.